Aquaporin-4 Expression in Meningioma Malignancy Progression - Pereira, Benedito Jamilson Araújo; Oba-Shinjo, Sueli M.; Aguiar, Paulo Henrique Pires de; Almeida, Antonio Nogueira de; Paiva, Wellingson da Silva; Marie, Suely Kazue Nagahashi (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Objectives The aim of the present study is to analyze if aquaporin-4 (AQP4) may also be a tumor progression marker for meningiomas.Methods This is an immunohistochemistry study realized at the Universidade de São Paulo, São Paulo, state of São Paulo, Brazil: frozen meningioma samples from 81 patients (57 females and 24 males, age range from 22 to 81 years old, average 56.5 ± 14.1 years old), including 57 meningiomas World Health Organization (WHO) grade I (GI); 19 grade II (GII), and 5 grade III (GIII) were analyzed. The relative expression level of AQP4 was analyzed by quantitative polymerase chain reaction (qPCR), using the SYBR Green approach and for staining detection. Tissue sections were routinely processed and subjected to antigen retrieval.Results The expression of AQP4 in meningioma samples ranged from 0 to 10.26, with a median of 0.001 in GI cases, of 0.008 in GII cases, and of 0.006 in GIII cases. Although not statistically significant (p = 0.942), GI meningiomas have a lower median AQP4 expression level than higher malignant grade cases.Conclusion The AQP4 gene and protein expressions presented no association with meningioma malignant progression.
Keywords: aquaporin-4; malignancy; meningioma